LNG-IUS vs. medical treatments for women with heavy menstrual bleeding: A systematic review and meta-analysis - Chen, Sijing; Liu, Jianhong; Peng, Shiyi; Zheng, Ying (Frontiers in Medicine, 2022)
Introduction To compare efficacy and safety of the levonorgestrel-releasing intrauterine system (LNG-IUS) with medical treatments for women with heavy menstrual bleeding. Materials and methods We searched PubMed, Embase, the Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure (CNKI), and Wanfang databases for relevant randomized controlled trials (RCTs) in November 2021. All meta-analyses were performed using the random-effects model. PROSPERO registration number: CRD42021295379. Results A total of trials (with 14 references) reporting on 1,677 women were included in this systematic review. The majority of the included RCTs were rated with low-to-unclear risk of bias in selection, detection, attrition, reporting, and other bias. All RCTs were rated as high risk in performance bias because blinding was difficult to ensure in the compared groups. Results of meta-analyses revealed that the number of clinical responders was greater in the LNG-IUS group than that in the medical treatments group at both 6-month (steroidal: five RCTs; n = 490; risk ratio [RR]: 1.72 [1.13, 2.62]; I2 = 92%; nonsteroidal: one RCT; n = 42; RR: 2.34 [1.31, 4.19]) and 12-month (steroidal: three RCTs; n = 261; RR: 1.31 [1.01, 1.71]; I2 = 74%) endpoints, with no clear differences on number of dropouts, and the incidence of adverse events. Conclusion Evidence indicates that LNG-IUS is superior to the medical treatments in short-term and medium-term clinical responses, blood loss control, compliance, and satisfaction. Meanwhile, frequency of adverse events related to LNG-IUS is acceptable. Systematic review registration PROSPERO, identifier CRD42021259335, https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021295379.